Ultrasound features of epibulbar malignancies of various histogenesis (melanoma and carcinoma) (Ukrainian Journal of Ophthalmology, 2025)
Purpose: To assess the ultrasound features of epibulbar malignancies of various histogenesis (melanoma and carcinoma), including the thickness of adjacent sclera and the sonographic density and dimensions of the neoplasm before and at various time points after radiation therapy plus cryosurgery.Material and Methods: Ultrasound (US) examination was performed in 75 patients with conjunctival melanoma (CM) or conjunctival carcinoma (CC) who underwent treatment at SI “The Filatov Institute of Eye Diseases and Tissue Therapy of the NAMS of Ukraine” in 2004-2021. Of these, 58 (77.3%) had CM, and 17 (24%) had CC. Of the patients with CM, 30 (51.7%) were men aged 18 to 88 years (median, 51.3 years), and 28 (48.3%) were women aged 26 to 87 years (median, 57.3 years). Of the patients with CC, 12 (70.6%) were men aged 28 to 82 years (median, 66.3 years), and 5 (29.4 %) were women aged 35 to 74 years (median, 57.0 years). US biomicroscopy images were obtained using the 50-MHz Aviso Ultrasound Platform. Dimensions and sonographic density of the tumor, thickness of the sclera underlying the tumor and scleral thickness on the opposite side were assessed at baseline and each 3 months over a one-year follow-up. All patients received radiation therapy (RT) plus cryosurgery (alias, cryodestruction of the tumor).Results: For the total study sample, the thickness of the sclera beneath the tumor was, on average, 1.9 times thinner compared to scleral thickness on the opposite side, and this difference was significant (p < 0.01). Eyes with partial resorption of CM exhibited a thickness of the underlying sclera (0.42 mm) that was 1.3 times and 1.2 times thinner compared to eyes with complete resorption of CM (χ2 = 3.13, р = 0.006) and eyes with partial resorption of CC (χ2 = 4.31, р = 0.01), respectively. A middle sonographic density was the most common category of sonographic density for CM as well as CC (χ2 = 3.1, р = 0.004; χ2 = 4.3, р = 0.006, respectively). There was a conjugation between the category of sonographic density and the presence of tumor recurrence in patients with CM or CC. Recurrence of CM or CC was observed only in tumors with a middle sonographic density (χ2 = 6.01, р = 0.004). A thickness of the sclera underlying the tumor not exceeding 0.30 mm may be considered as a risk factor for the development of scleromalacia (odds ratio (OR) = 7.7, 95% confidence interval (CI) 3.2-53.8) (Copyright Registration Certificate for a Work No. 134003 issued on March 3, 2025).Conclusion: The thickness of the sclera beneath the tumor as assessed by US was thinner compared to scleral thickness on the opposite side. A middle sonographic density was the most common category of sonographic density for CM. There was a conjugation between the category of sonographic density and the presence of tumor recurrence in patients with CM and those with CC. Recurrence of CM or CC was observed only in tumors with a middle sonographic density. A thickness of the sclera underlying the tumor not exceeding 0.30 mm may be considered as a risk factor for the development of scleromalacia (OR = 7.7, 95% CI 3.2-53.8).
Keywords: ocular oncology; conjunctival melanoma; conjunctival carcinoma; ultrasound examination; radiation therapy; cryodestruction; radiation therapy plus cryosurgery; sclera; epibulbar neoplasm